2023
DOI: 10.1039/d3fd00038a
|View full text |Cite
|
Sign up to set email alerts
|

Real-time visualisation of ion exchange in molecularly confined spaces where electric double layers overlap

Abstract: Ion interactions with interfaces and transport in confined spaces, where electric double layers overlap, are essential in many areas, ranging from crevice corrosion to understanding and creating nano-fluidic devices at...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Nano-restricted water, in addition to studying the density, electrical conductivity and other physical properties of water, one of the research directions should be the structure of the bilayer, and it has been found [47] that there is specific adsorption in the inner bilayer with weak receptor sites. This adsorption can change the local concentration in the nano-restricted volume, while the layers of nano-restricted space overlap on both sides of the wall if the radius of the nano-restricted space is less than half the thickness of the bilayer.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Nano-restricted water, in addition to studying the density, electrical conductivity and other physical properties of water, one of the research directions should be the structure of the bilayer, and it has been found [47] that there is specific adsorption in the inner bilayer with weak receptor sites. This adsorption can change the local concentration in the nano-restricted volume, while the layers of nano-restricted space overlap on both sides of the wall if the radius of the nano-restricted space is less than half the thickness of the bilayer.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%